Electroadsorption Desalination with Carbon Nanotube/PAN-Based Carbon Fiber Felt Composites as Electrodes - Yang Liu; Junbo Zhou (The Scientific World Journal)
The chemical vapor deposition method is used to prepare CNT (carbon nanotube)/PCF (PAN-based carbon fiber felt) composite electrodes in this paper, with the surface morphology of CNT/PCF composites and electroadsorption desalination performance being studied. Results show such electrode materials with three-dimensional network nanostructures having a larger specific surface area and narrower micropore distribution, with a huge number of reactive groups covering the surface. Compared with PCF electrodes, CNT/PCF can allow for a higher adsorption and desorption rate but lower energy consumption; meanwhile, under the condition of the same voltage change, the CNT/PCF electrodes are provided with a better desalination effect. The study also found that the higher the original concentration of the solution, the greater the adsorption capacity and the lower the adsorption rate. At the same time, the higher the solution’s pH, the better the desalting; the smaller the ions’ radius, the greater the amount of adsorption.